O Prędkościach Fali Kulistej w Izotropowym Materiale Sprężystym - Wesołowski, Z. (Engineering Transactions, 1975)
Using the theory discontinuity surfaces the spherical acceleration wave is constructed. Subsequently, the moving spherical wave is built and phase and group velocities are evaluated. It was shown that the phase velocity is greater than the propagation velocity and group velocity. For sufficiently large frequencies the propagation velocity is the geometric mean of the phase and group velocities. It was also demonstrated that the velocity of signal is smaller than the propagation velocity. It was proved that the spherical wave is a sum of plane waves and the plane wave is a sum of spherical waves.